Enhancing lateritic soil performance with cement and calcined limestone dust for road base application - Khin Sam Thwe; Jiratchaya Ayawanna; Lindung Zalbuin Mase; Salisa Chaiyaput (Scientific Reports, 2026)
Lateritic soils are widely used in road construction in tropical regions, but their natural engineering properties often require stabilization to meet strength and performance requirements. In Thailand, lateritic soils are commonly stabilized with cement-based binders, which are applied as soil-cement subbase and soil-cement base layers in accordance with the Department of Highways (DOH) specifications. This study evaluates the stabilization of lateritic soil using ordinary Portland cement (OPC) with calcined limestone dust (CLD) as a partial cement replacement. CLD is produced by the calcination of limestone dust, which is a quarry by-product, at elevated temperatures. In the proposed stabilization approach, 20% of OPC was replaced with CLD to assess its effect on the stabilized soil's physical and mechanical properties. Laboratory tests included Atterberg limits, compaction characteristics (optimum moisture content and maximum dry density), and unconfined compressive strength (UCS). The results indicate that the combined use of OPC and CLD reduces soil plasticity and slightly modifies compaction behavior due to changes in particle packing and moisture demand. Stabilization significantly improves UCS, and mixtures containing 20% CLD achieve compressive strengths comparable to fully cement-stabilized samples after 28 days of curing. Strength enhancement is primarily attributed to cement hydration, which forms calcium silicate hydrate, while CLD contributes through filler and nucleation effects, resulting in a denser microstructure suitable for road base applications.
Keywords: Concrete and Cement Materials Research; Geotechnical and construction materials studies; Soil and Unsaturated Flow